The Captive Prince - or- Liberty run Mad. - (:unkn) unknown (Grant, 1782)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820